2001
DOI: 10.1023/a:1004850919647
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We have made substantial advances in elucidating the properties of the susceptibility of the square lattice Ising model. We discuss its analyticity properties, certain closed form expressions for subsets of the coefficients, and give an algorithm of complexity O(N 6 ) to determine its first N coefficients. As a result, we have generated and analyzed series with more than 300 terms in both the high-and low-temperature regime. We quantify the effect of irrelevant variables to the scaling-amplitude functions. In … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
196
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(208 citation statements)
references
References 50 publications
11
196
0
1
Order By: Relevance
“…We have also performed low, and high, series expansions for theĈ j (N, N ) defined by equations (4.2) in [14] (see also (20)), and we also found that these series identify with the one of h 2j (N ) and h 2j+1 (N ) with the normalization :…”
Section: Series Solution Of the Sigma Form Of Painlevé VImentioning
confidence: 72%
See 3 more Smart Citations
“…We have also performed low, and high, series expansions for theĈ j (N, N ) defined by equations (4.2) in [14] (see also (20)), and we also found that these series identify with the one of h 2j (N ) and h 2j+1 (N ) with the normalization :…”
Section: Series Solution Of the Sigma Form Of Painlevé VImentioning
confidence: 72%
“…Recalling relations like (5.7)-(5.11) of [14], all these identities can also be written in terms of the nome of the elliptic functions occurring in the Ising model. These identities, now, become remarkable identities on some infinite Gaussian sums, or on For N = 0 this equation has been solved in terms of theta functions [40,41,42], has dihedral symmetry and has a countable number of algebraic solutions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6,7 Taking the anisotropic "Hamiltonian limit" 8,9 in which the classical Ising model reduces to the quantum Ising model ͑1͒, one can show that the expressions of Wu et al reduce to Eq. ͑19͒ ͑details will be given elsewhere͒.…”
Section: Linear Chainmentioning
confidence: 99%